What do Cochrane systematic reviews say about therapeutic tinnitus interventions? - Person, Osmar Clayton (2022)
Introduction: Tinnitus is a sound perception not related to stimulation. It can significantly impair the quality of life and its treatment is considered one significant challenge of Medicine. Objective: To evaluate systematic reviews developed by Cochrane regarding therapeutic interventions for subjective tinnitus. Methods: It is an overview of Cochrane systematic reviews. We searched systematic reviews on Cochrane Library. The MeSH term "tinnitus" was used for searches. Inclusion criteria involved therapeutic interventions for patients with subjective tinnitus. Results: The search strategy recovered 577 citations with 14  Cochrane systematic reviews. 13 were included because they were focusing on primary tinnitus interventions. One review had no scope of analysis for tinnitus and it was excluded. 7,998 tinnitus patients were evaluated. Conclusion: There is a lack of evidence of the effectiveness of any intervention for tinnitus treatment, considering the studies performed so far and compiled in Cochrane systematic reviews.